FACTORS AFFECTING NET INVESTMENT OF FOREIGN INVESTORS IN THE STOCK EXCHANGE OF THAILAND - Ragappai, Narin; Pongsupatt, Tharinee (Journal of Buddhist Education and Research (JBER), 2023)
The objective of this independent study is to find out the factors that affecting net investment of foreign investors in the Stock Exchange of Thailand. This study uses monthly secondary data from January 2017 to December 2021 totally 60 data set. Data was analyzed by multiple linear regression model with ordinary least square. The factors that involve to this study are net investment of foreign investors, corruption perceptions index, consumer price index, financial Times Stock Exchange 100 Index, import export price index, the spread between Thai and US interest rates. and the exchange rate between Baht and US dollar. The result of this study found that only three factors affecting net investment of foreign investors in the Stock Exchange of Thailand; financial Times Stock Exchange 100 Index (FTSE100) with statistically positive relationships while the spread between Thai and US interest rates. And the exchange rate between Baht and US dollar shown negative relationships of net investment of foreign investors in the Stock Exchange of Thailand.